2018
DOI: 10.1590/s1806-37562017000000328
|View full text |Cite
|
Sign up to set email alerts
|

Trend of self-reported asthma prevalence in Brazil from 2003 to 2013 in adults and factors associated with prevalence

Abstract: Objectives: To determine the trend of self-reported asthma diagnosed prevalence and to describe the factors associated with asthma in Brazilian adults. Method: Epidemiological cross-sectional study based on databases analysis from three national household surveys: Pesquisa Nacional por Amostra de Domicílios (PNAD) 2003, PNAD 2008 and Pesquisa Nacional de Saúde (PNS) 2013. Participants between 18-45 years old were included. Trend analysis of asthma diagnosed prevalence was conducted using a logistic general li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
4
4
1
6
Order By: Relevance
“…This study revealed that urban residents (AOR: 1.5; 95% CI 1.3–3.90) were more likely to develop bronchial asthma than rural residents. It was consistent with the report in Brazil and Ethiopia [15, 16]. This might be explained outdoor air of urban area is highly polluted due to high levels of traffic and industry related emissions that could increase the risk of asthma.…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that urban residents (AOR: 1.5; 95% CI 1.3–3.90) were more likely to develop bronchial asthma than rural residents. It was consistent with the report in Brazil and Ethiopia [15, 16]. This might be explained outdoor air of urban area is highly polluted due to high levels of traffic and industry related emissions that could increase the risk of asthma.…”
Section: Discussionsupporting
confidence: 92%
“…In a cross-sectional study based on household surveys conducted in Brazil in 2003, 2008, and 2013, the prevalence of asthma was consistently higher in women, 1 as was the case in our study. This might be explained by biological differences, such as sex hormones and increased bronchial hyperresponsiveness, and social factors, such as different perceptions of airflow obstruction and medication compliance.…”
Section: To the Editorsupporting
confidence: 83%
“…The prevalence of asthma among adults is poorly known, especially in vulnerable regions, such as the Brazilian Amazon. 1 The objective of this study was to estimate the prevalence of self-reported asthma in adults living in the metropolitan area of Manaus, Brazil, in 2015.…”
Section: To the Editormentioning
confidence: 99%
“…From this perspective, given the two-way relationship, the importance of increasing the levels of physical activity is highlighted: to improve health status of asthmatics and to protect health individuals against the development of asthma. Such prevalence of 6.45% is high compared to that found in a study of a population sample in Brazil, which showed a self-reported prevalence of 2.16% among women (46). In the USA, a populational-based study conducted in a population sample (n=3,840) found that most adults with self-reported asthma were physically inactive and that physical inactivity appears to be associated with an increased prevalence of asthma, which was of 9.0% (47).…”
Section: Prevalence Of Health Problems and Physical Activity Levelscontrasting
confidence: 59%